2014
DOI: 10.7755/fb.112.2-3.7
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal distribution and abundance of cetaceans off Southern California estimated from CalCOFI cruise data from 2004 to 2008

Abstract: Abstract-Documenting year-round diversity and distribution of marine mammals off Southern California is important for assessment of effects of potentially harmful anthropogenic activities. Although the waters off Southern California have been surveyed extensively for marine mammals over the past 18 years, such surveys have been periodic and were conducted primarily from summer to fall, thereby missing potential seasonal shifts. We examined seasonal abundance and population density of cetaceans off Southern Cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 41 publications
1
19
0
Order By: Relevance
“…The overall study area abundance estimates are similar to those derived previously using line-transect analyses (Campbell et al, 2015), but the habitat models provide fine-scale detail in spatial density patterns that are more useful for conservation and management applications. Given the increased use of SDMs to help evaluate and reduce potential risks to cetaceans (e.g., Redfern et al, 2013; U.S. Department of the Navy, 2015), and the documented high degree of seasonal variability in the distribution of cetaceans in the study area (Dohl et al, 1986;Green et al, 1992Green et al, , 1993Forney and Barlow, 1998;Becker et al, 2014;Douglas et al, 2014;Henderson et al, 2014;Campbell et al, 2015), it is critical to develop seasonally-explicit SDMs. Campbell et al (2015) were able to provide separate linetransect abundance estimates for winter and spring seasons; however, in our study sighting data were not sufficient to develop separate habitat models for the two cool seasons.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The overall study area abundance estimates are similar to those derived previously using line-transect analyses (Campbell et al, 2015), but the habitat models provide fine-scale detail in spatial density patterns that are more useful for conservation and management applications. Given the increased use of SDMs to help evaluate and reduce potential risks to cetaceans (e.g., Redfern et al, 2013; U.S. Department of the Navy, 2015), and the documented high degree of seasonal variability in the distribution of cetaceans in the study area (Dohl et al, 1986;Green et al, 1992Green et al, , 1993Forney and Barlow, 1998;Becker et al, 2014;Douglas et al, 2014;Henderson et al, 2014;Campbell et al, 2015), it is critical to develop seasonally-explicit SDMs. Campbell et al (2015) were able to provide separate linetransect abundance estimates for winter and spring seasons; however, in our study sighting data were not sufficient to develop separate habitat models for the two cool seasons.…”
Section: Discussionmentioning
confidence: 99%
“…Five different research vessels were used during the survey period, but Douglas et al (2014) found no significant difference in perpendicular distance to transect line for vessels with varying platform height. All surveys were conducted in passing mode (i.e., when a cetacean/cetacean group is sighted the ship continues on course and is not diverted to the vicinity of the sighting) with two dedicated observers searching for cetaceans FIGURE 1 | CalCOFI sampling stations (yellow circles) and the approximate 385,460 km 2 study area (black bold line) used to develop the winter/spring species distribution models presented in this study.…”
Section: Study Area and Field Methodsmentioning
confidence: 99%
See 3 more Smart Citations